Myelin damage and cortical atrophy in watershed regions in patients with moyamoya angiopathy - Filimonova, Elena; Ovsiannikov, Konstantin; Sosnov, Alexsey; Perfilyev, Artem; Gafurov, Rustam; Galaktionov, Dmitriy; Bervickiy, Anatoliy; Kiselev, Vitaly; Rzaev, Jamil (Frontiers in Neuroscience, 2022)
Background: Despite it being known that chronic ischemia results in myelin damage and gray matter atrophy, data regarding patients with moyamoya angiopathy is limited. We hypothesized that chronic ischemia in moyamoya angiopathy leads to myelin damage, especially in anterior watershed regions, as well as cortical atrophy in these areas. Methods: Twenty adult patients with moyamoya angiopathy and 17 age- and sex-matched healthy controls were evaluated using the T1w/T2w mapping method and surface-based MR-morphometry. The T1w/T2w signal intensity ratio, which reflects the white matter integrity, and the cortical thickness, were calculated in watershed regions and compared between the patients and controls. In the patients with moyamoya angiopathy, the correlations between these parameters and the Suzuki stage were also evaluated. Results: The regional T1w/T2w ratio values from centrum semiovale in patients with MMA were significantly lower than those in healthy controls (p < 0.05); there was also a downward trend in T1w/T2w ratio values from middle frontal gyrus white matter in patients compared with the controls (p < 0.1). The cortical thickness of the middle frontal gyrus was significantly lower in patients than in healthy controls (p < 0.05). There were negative correlations between the Suzuki stage and the T1w/T2w ratio values from the centrum semiovale and middle frontal white matter. Conclusion: T1w/T2w mapping revealed that myelin damage exists in watershed regions in patients with moyamoya angiopathy, in association with cortical atrophy according to MR-morphometry. These changes were correlated with the disease stage.